2006
DOI: 10.1093/pasj/58.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Chandra and XMM-Newton Observations of a Group of Galaxies, HCG 62

Abstract: We present results from Chandra and XMM-Newton observations of a bright group of galaxies, HCG 62. There are two cavities at about $30{}^{\prime\prime}$ northeast and $20{}^{\prime\prime}$ southwest of the central galaxy in the Chandra image. The energy spectrum shows no significant change in the cavity compared with that in the surrounding region. The radial X-ray profile is described by the sum of the 3-$\beta$ components with core radii of about 2, 10, and 160 kpc. We studied the radial distributions of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
61
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 64 publications
22
61
2
Order By: Relevance
“…The observed O and Mg abundances are mostly consistent with those derived from Chandra and XMM-Newton (Buote, 2002;Morita et al 2006;Hayakawa et al 2006). Due to the better sensitivity to O and Mg lines, the XIS results are significantly better than those from other satellites, especially at low surface brightness.…”
Section: Abundance Pattern Of Icm In Clusters Of Galaxiessupporting
confidence: 82%
“…The observed O and Mg abundances are mostly consistent with those derived from Chandra and XMM-Newton (Buote, 2002;Morita et al 2006;Hayakawa et al 2006). Due to the better sensitivity to O and Mg lines, the XIS results are significantly better than those from other satellites, especially at low surface brightness.…”
Section: Abundance Pattern Of Icm In Clusters Of Galaxiessupporting
confidence: 82%
“…Chandra and XMM-Newton observations (e.g., McNamara et al 2000) have revealed the existence of giant cavities in clusters, which are often associated with radio emission from ongoing jet activity of the central AGN, actively inflating these ''bubbles.'' This direct link has also been observed on the smaller group (e.g., Morita et al 2006) and galaxy scales (e.g., Finoguenov & Jones 2001;Diehl & Statler 2007, 2008a, 2008b. AGN outbursts have been shown to have potentially more than sufficient energy to offset cooling in a large fraction of clusters (Bîrzan et al 2004), and even in normal elliptical galaxies and groups (Best et al 2005(Best et al , 2006.…”
Section: Introductionmentioning
confidence: 78%
“…This result is consistent with what is seen in brightest cluster galaxies in clusters without strong cooling flows by Egami et al (2006). Those clusters frequently have evidence for AGN activity that apparently injects energy into the ICM and prevents cooling; the large X-ray bubbles in HCG 62 indicate similar activity (e.g., Morita et al 2006). …”
Section: Evolutionary Stages Of Compact Groups In This Samplementioning
confidence: 99%